PERANAN PEMERINTAH DAERAH DALAM PENINDAKAN GANGGUAN KETERTIBAN UMUM DAN KETENTARAM MASYARAKAT DI KAWASAN TEROWONGAN NUR MENTAYA - Arifudin, Arifudin; Bangas, Karlinae D; Januardy, Ivans (Legacy: Jurnal Hukum dan Perundang-Undangan, 2025)
This research analyzes the role of the Regional Government in handling disturbances of public order and community tranquility, focusing on the implementation of Regional Regulation Number 10 of 2021 of Kotawaringin Timur Regency in the strategic area of the Nur Mentaya Tunnel. The context of regional autonomy demands local governments to realize a safe and orderly community life, with the Public Order Agency (Satpol PP) as the frontline enforcement of regional regulations. The Nur Mentaya Tunnel area, as a vital public space, requires strict supervision to prevent disturbing behaviors. Therefore, this research aims to analyze the legal basis of Regional Regulation Number 10 of 2021, the role of local law enforcement actors (including the Integrated Team), as well as the legal challenges in enforcing public order disturbances. This research analyzes the role of the Regional Government in handling disturbances of public order and community tranquility, focusing on the implementation of Regional Regulation Number 10 of 2021 of Kotawaringin Timur Regency in the strategic area of the Nur Mentaya Tunnel. The context of regional autonomy demands local governments to realize a safe and orderly community life, with the Public Order Agency (Satpol PP) as the frontline enforcement of regional regulations. The Nur Mentaya Tunnel area, as a vital public space, requires strict supervision to prevent disturbing behaviors. Therefore, this research aims to analyze the legal basis of Regional Regulation Number 10 of 2021, the role of local law enforcement actors (including the Integrated Team), as well as the legal challenges in enforcing public order disturbances.